Detection of Hemoglobin New York [β113 (G15) Val→Glu, GTG>GAG] in a Thai Woman by Capillary Electrophoresis - Panyasai S. (2017)
© 2016, Indian Society of Haematology & Transfusion Medicine. Hemoglobin (Hb) New York [β113 (G15) Val→Glu, GTG > GAG] is a very rare β-chain variant found in Thailand. This variant is often missed by routine laboratory testing because Hb New York and Hb A have the identical retention time on high performance liquid chromatography. We reported here for the first time that the detection of Hb New York in a Thai woman by using capillary electrophoresis (CE). A peak of Hb New York located ahead of Hb A at the electrophoretic zone 11 with a level of 42.8 %. The DNA sequencing revealed the GTG > GAG mutation at codon 113 for Hb New York on one allele of β-globin gene. Therefore, the CE has a high efficiency to prevent the misinterpretation of hemoglobin analysis in patients who are heterozygote of this variant.